Survey on sexual health for male patients with acute myocardial infarction and percutaneous transluminal coronary angioplasty plus stent implantation - Li, Q.; Jiang, Y.; Pan, H.-L.; Li, L.; Cai, L.-M.; Fang, H.-Y. (Heart, 2013)
Objectives The survey is based on status of sexual health and sexual needs for male patients with acute myocardial infarction and Percutaneous Transluminal Coronary Angioplasty (PTCA) plus stent implantation. The survey data provides the basis for guiding patients' health education. Methods General questionnaire, sexual knowledge status questionnaire and sexual health knowledge demand questionnaire were carried out by 214 cases of patients with PTCA plus stent implantation. Collected data entered into a database for statistical analysis. Results The sexual health overall score of 214 patients is 8.79 ± 2.52. There is a statistically significant difference (P < 0.05) in different education level, occupation and monthly income. There is no statistically significant difference (P > 0.05) in different age. The knowledge of sexual health demand overall score is 29.40 ± 6.47. There is a statistically significant difference (P < 0.05) in different age, education level and occupation. There is no statistically significant difference (P > 0.05) in different monthly income. Conclusions Patients with PTCA plus stent implantation, the sexual knowledge cognitive level is low. For the higher demand of sexual health knowledge, the medical personnel should strengthen the knowledge of sex education for patients to improve the quality of sex.
Keywords: Asia; acute heart infarction; cardiology; data base; education; health; health education; heart; human; implantation; income; male; medical personnel; occupation; patient; prevention; questionnaire; rehabilitation; sexual education; sexual health; statistical analysis; stent; transluminal coronary angioplasty